PENGARUH LIMBAH CAIR INDUSTRI TAHU TERHADAP KUALITAS AIR SUNGAI PAAL 4 KECAMATAN TIKALA KOTA MANADO - , Sepriani; Abidjulu, Jemmy; Kolengan, Harry S. J. (Sam Ratulangi University, 2016)
A research had been conducted to determine the pollutan level of Paal 4 river water in Tikala Manado, as a results of tofu liquid waste discharging. The measured parameters are pH, nitrite (NO2-), nitrate (NO3-), ammonium, total dissolved solids (TDS ), total suspended solids (TSS), dissolved oxygen (DO), chemical oxygen demand (COD) and biochemical oxygen demand (BOD). The results showed that almost all of measured parameters, that is pH (4.95), nitrate (232.6082 mg/L), ammonium (0.6533 mg/L), TDS (3510 mg/L), DO (0.83 mg/L), BOD (370 mg/L) and COD (420 mg/L), exceed the requirement set by government in PP No. 82 thn 2001. This indicates that the river water is in a highly polluted condition.Telah dilakukan penelitian untuk menentukan tingkat pencemaran air sungai Paal 4 di Tikala Manado hasil pembuangan limbah cair tahu. Parameter yang diukur adalah pH, nitrit (NO2-), nitrat (NO3-), amonium, total padatan terlarut (TDS), total padatan tersuspensi (TSS), oksigen terlarut (DO), kebutuhan oksigen kimiawi (COD) dan kebutuhan oksigen biokimiawi (BOD). Hasil penelitian menunjukan hampir semua parameter yang diukur yaitu pH (4.95), Nitrat (232.6082 mg/L), Amonium (0.6533 mg/L), TDS (3510 mg/L), DO (0.83 mg/L), BOD (370 mg/L) dan COD (420 mg/L) melebihi standar yang telah ditetapkan oleh pemerintah dalam PP No. 28 thn 2001. Hal ini mengindikasikan bahwa air sungai ini berada pada kondisi sangat tercemar.